Communicative Competence In Teaching Speaking - Susanto, Jasno (Journal of English and Arabic Language Teaching, 2012)
The existence of Communicative Competence in teaching speaking is importantly viewed as the basis as well as the goal that must be achieved. Understanding the aspects and characteristics of Communicative Competence can help the speaking teachers to guide their learners into speaking atmosphere that make them speak naturally. Negotiation of meaning and management of interaction in communicative competence reflect to the focus on the use of language, not on the usage. Oral communicative tasks given to students are the speaking teachers’ consideration to create students’ orally natural communication.